Accurate diagnosis of degree of atypia in cholangiocarcinoma by peroral cholangioscopy‐guided probe‐based confocal endomicroscopy. Issue 1 (22nd November 2019) - Tanisaka, Yuki; Ryozawa, Shomei; Nonaka, Kouichi
Abstract : Watch a video of this article